6-x-1=6-(x+1)

Simple and best practice solution for 6-x-1=6-(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-x-1=6-(x+1) equation:


Simplifying
6 + -1x + -1 = 6 + -1(x + 1)

Reorder the terms:
6 + -1 + -1x = 6 + -1(x + 1)

Combine like terms: 6 + -1 = 5
5 + -1x = 6 + -1(x + 1)

Reorder the terms:
5 + -1x = 6 + -1(1 + x)
5 + -1x = 6 + (1 * -1 + x * -1)
5 + -1x = 6 + (-1 + -1x)

Combine like terms: 6 + -1 = 5
5 + -1x = 5 + -1x

Add '-5' to each side of the equation.
5 + -5 + -1x = 5 + -5 + -1x

Combine like terms: 5 + -5 = 0
0 + -1x = 5 + -5 + -1x
-1x = 5 + -5 + -1x

Combine like terms: 5 + -5 = 0
-1x = 0 + -1x
-1x = -1x

Add 'x' to each side of the equation.
-1x + x = -1x + x

Combine like terms: -1x + x = 0
0 = -1x + x

Combine like terms: -1x + x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 7-4x-2x=-35 | | (-4x)+(-3x)+x= | | 5c-1=34 | | -(-6y-3z+6)= | | (x^4)-4(x^3)+7=0 | | .08x=13-0.5x | | 4k(k+1)=25 | | -4x-6+5x=-10 | | (3x+9)-16=-5 | | 29=4x-7 | | 6x=-2x-2 | | (3x+9)-16=5 | | 11y+1.9= | | 20a^5b^3+30a^3b^2-40a^2b^3= | | 10+6x-2x=50 | | -4t-2+7t=4 | | -4x-8=8x+16 | | 4(x+14)= | | 5.6=-1+x | | 5x+1+5x=-99 | | 7x-1=9x-6 | | 5x-2(5+2x)=3+x-8 | | bx-6x=4a-ax | | -(6y-3z+6)= | | x^2+2mx-(m-20)=0 | | 2(3x+y)=(2x+5y) | | 6x+1=6(x+7) | | 8x+1=6(x+7) | | 12x^3+3x^2-8x-2=0 | | 24x=59 | | (9+2x)=40 | | 26+29x=28+28x |

Equations solver categories